Properties of X-ray detected far-IR AGN in the green valley. Issue Volume 15:Issue S356(2019) (October 2019) - Mahoro, Antoine; Pović, Mirjana; Väisänen, Petri; Nkundabakura, Pheneas; Nyiransengiyumva, Beatrice; van der Heyden, Kurt
Abstract: In this study, we analysed active galactic nuclei in the "green valley" by comparing active and non-active galaxies using data from the COSMOS field. We found that most of our X-ray detected active galactic nuclei with far-infrared emission have star formation rates higher than the ones of normal galaxies of the same stellar mass range.